Kualitas Laporan Keuangan Pemerintah: Cerminan Pertumbuhan Ekonomi Dan Tata Kelola Yang Baik - Rasyidah; Dara Angreka Soufyan; Rimal Mahdani; Diah Tri Wahyuni; Irdayani; Iwan Pelita Kasim (Yayasan Sagita Akademia Maju, 2024)
This study examines the impact of Gross Domestic Product (GDP) and the Corruption Perception Index (CPI) on the quality of local government financial reports in Indonesia. The results of the multiple linear regression indicate that GDP exerts a positive and significant influence on the quality of financial reporting. Nonetheless, CPI exerts minimal influence under this model. The study's limitations encompass restricted sample coverage and reliance on the CPI as the sole governance measure. Further research should aim to broaden the sample coverage and incorporate additional pertinent variables to enhance the comprehension of the determinants affecting the quality of financial reports.